TOPOGRAPHIC ASPECTS IN THE SPATIAL AND TEMPORAL DYNAMIC OF NET RADIATION - Filgueiras, Roberto; Nicolete, Donizeti A. P. [UNESP]; Carvalho, Tania M. de; Cunha, Antonio R. da [UNESP]; Zimback, Celia R. L. [UNESP] (Soc Brasil Engenharia Agricola, 2017)
The measurements obtained by remote sensing are influenced by issues related to relief. Based on that, this paper aims to analyze the spatial and temporal dynamics of the net radiation (Rn), considering the influence of topographic parameters on it, in Edgardia Experimental Farm (FEE). It was used the methodology based on the SEBAL algorithm (Surface Energy Balance Algorithm for Land) to estimate the net radiation by orbital images. In order to assess the topographic influence on the computing of net radiation, three methodologies were applied: without topographic correction (RnSem), cosine correction (RnCos) and C correction (RnC). These methodologies were applied on 21 images of the orbital platform Landsat-5/TM, from 1985 up to 2010. Due to the complex relief of the FEE, the cosine correction did not show effectiveness on the attenuation of topographic influence. For the values of RnC, we noticed an average reduction of 5.97% for the standard deviation, relative to the images without correction. These results show the importance of considering the relief, to achieve higher accuracies on the estimation of biophysical parameters with orbital images.
Keywords: topographic correction; SEBAL; biophysical parameters